(3aj GSS GdeMGSHI GdeGdjI (B/s - (3GHh RjO, ceGd NdjaIs; (3HOhj, eMeO YHGS s ((3GdGScfOQjI(B: s (3GdOGQ GdLGeYjI(B, s, 1999)
(3ebOeI Yf GdeMGSHI haQhYgG , GdHfGA GdfXQj ddeMGSHI GdeGdjI , GdeYGOdIGJ GdeMGSHjI GdQFjSjI , CgOGa GdbhGFe GdeGdjI hYfGUQgG , GdOhQI GdeMGSHjI hCQcGfgG $1 (3GSJceGd GdOhQI GdeMGSHjI , JShjI hGYOGO GdbhGFe GdeGdjI , GSJceGd GdOhQI GdeMGSHjI , GbaGd GdMGSHGJ hhQbI GdYed , GdeMGSHI aj GdeTQhY GdJLGQj , GdJMUjd hGdSOGO HGSJNOGe GdGhQGb GdJLGQjIs
Keywords: (3GdChQGb GdJLGQjIs; (3GdeMGSHI GdJMdjdjIs